2012
DOI: 10.1038/jid.2012.43
|View full text |Cite
|
Sign up to set email alerts
|

The Human Skin Barrier Is Organized as Stacked Bilayers of Fully Extended Ceramides with Cholesterol Molecules Associated with the Ceramide Sphingoid Moiety

Abstract: The skin barrier is fundamental to terrestrial life and its evolution; it upholds homeostasis and protects against the environment. Skin barrier capacity is controlled by lipids that fill the extracellular space of the skin's surface layer--the stratum corneum. Here we report on the determination of the molecular organization of the skin's lipid matrix in situ, in its near-native state, using a methodological approach combining very high magnification cryo-electron microscopy (EM) of vitreous skin section defo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
230
5
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(266 citation statements)
references
References 33 publications
21
230
5
2
Order By: Relevance
“…Simulations [48] show that galactosylceramides occupy an area/lipid similar to sphingomyelin in bilayers containing sphingomyelin and CHOL, which is much larger than the typical area/molecule in the SC membranes. The presence of this large sugar moiety will disfavour the extended tail arrangement seen in some CER crystal structures and hypothesized in some models of SC lipid arrangement [12], and make hydrated bilayers thermodynamically stable. Only once the unilamellar vesicles have been transported out of the cells is the sugar moiety removed, which then can lead to a gel-like membrane; at this point, the vesicles seem to lose internal water and fold into a stacked disc-like structure [7].…”
Section: (B) Summarymentioning
confidence: 94%
“…Simulations [48] show that galactosylceramides occupy an area/lipid similar to sphingomyelin in bilayers containing sphingomyelin and CHOL, which is much larger than the typical area/molecule in the SC membranes. The presence of this large sugar moiety will disfavour the extended tail arrangement seen in some CER crystal structures and hypothesized in some models of SC lipid arrangement [12], and make hydrated bilayers thermodynamically stable. Only once the unilamellar vesicles have been transported out of the cells is the sugar moiety removed, which then can lead to a gel-like membrane; at this point, the vesicles seem to lose internal water and fold into a stacked disc-like structure [7].…”
Section: (B) Summarymentioning
confidence: 94%
“…The comparison between the images obtained using a conventional preparation and CEMOVIS showed differences in the organization of bacterial DNA and cell wall of Mycobacterium smegmatis [35] and Shigella flexneri [42] and presented new insights into the morphology of bacteria [32,[43][44][45]. This technique enabled to show details of the design of melanosomes [46], the human skin barrier [47] and the molecular architecture of cadherins in native epidermal desmosomes [34].…”
Section: Cryo-electron Microscopy Of Vitreous Sectionsmentioning
confidence: 96%
“…Previous studies described separation of cholesterol from the lamellar phases (Mojumdar et al, 2015b;Schreiner et al, 2000); however, the physiological relevance of this separation is not known. In contrast, recent study using very high resolution electron microscopy on vitreous skin sections found no cholesterol crystals (Iwai et al, 2012). Cholesteryl sulphate, that is, ester of sulphuric acid with cholesterol, is a minor component of the stratum corneum lipid matrix; it is present in approximately 5% of the barrier lipids (or approximately 2% of all lipids including surface lipids (Lampe et al, 1983)).…”
Section: Composition Of the Skin Lipid Barriermentioning
confidence: 96%
“…4). Although the extended conformation is not common in biological membranes, it could be advantageous for the stratum corneum barrier properties (Corkery, 2002;Iwai et al, 2012). First, it would reduce the packing strain of ceramide because they have a smaller cross-section of the polar head than of the chains and there are no lipids with bulky polar heads to compensate for such unfavourable packing ratio of hairpin ceramide.…”
Section: Molecular Arrangement Of the Skin Lipid Barriermentioning
confidence: 99%